Предмет: Математика,
автор: ksudenkov
(x+2)(x+3)=6 решить через дискриминант
Ответы
Автор ответа:
0
1). (х+2)(х+3)=х^2+3х+2х+6=х^2+5х+6
2). х^2+5х+6=6
х^2+5х+6-6=0
х^2+5х=0
а=1, в=5, с=0
D=5^2-4*1*0
D=5^2
D=25
х1=(-5+5):2=0:2=0
х2=(-5-5):2=-10:2=-5
Ответ: -5;0
2). х^2+5х+6=6
х^2+5х+6-6=0
х^2+5х=0
а=1, в=5, с=0
D=5^2-4*1*0
D=5^2
D=25
х1=(-5+5):2=0:2=0
х2=(-5-5):2=-10:2=-5
Ответ: -5;0
Похожие вопросы
Предмет: Английский язык,
автор: ruslanakramov2017
Предмет: Русский язык,
автор: mataevbaisangur
Предмет: Химия,
автор: berly95
Предмет: Алгебра,
автор: nataharu33
Предмет: Химия,
автор: olyakrivkova9олечка